Microbial assessment of surfaces and air quality in emergency and gynecology operation theater of Bahawal Victoria Hospital - Saif Ur Rehman; Shumaila Nazuk; Eqaza Javed; Nayab Khalid (AMMANIF, 2022)
Background: Microorganisms present in air and on surfaces of operation theaters are the common cause of nosocomial infection in patients. Microbiological assessment of organisms is important to check the quality of environment provided to patients who are already in compromised state. So, this study was conducted to determine the level of bacterial contamination of air, environmental and medical equipment surfaces in operation theatres of Bahawal Victoria Hospital, Bahawalpur. Objective: To determine Microbes of surfaces and air quality in Emergency and Gynecology operation theater of Bahawal Victoria Hospital. Methodology: A descriptive cross-sectional analytical study performed involving 100 samples from air and surfaces of Gynecology and Emergency operation theater of BVH from July 2015 to Dec 2015. Demographic and other clinical data was collected using standardized data collection tools. Culture of air and different sites [floor, walls, basin and equipment) for the microbiological assessment was done by the gold standard method. Culture positive organisms were confirmed by gram staining, microscopy and biochemical tests. Results: Of the100 samples collected from different sites like air, basin, walls, floor and instruments of emergency operation theater and Gynecology Operation Theater most organisms collected from theatres were Staphylococcus aureus followed by E. coli and K. pneumonia respectively. Most organisms were isolated from air, basin, and floor while medical equipment were fully sterilized and their samples show no growth.